From He-Cession to She-Stimulus? The labor market impact of fiscal policy across gender - Alica Ida Bonk; Laure Simon (SERIEs - Journal of the Spanish Economic Association, 2022)
Men, especially those that are young and less educated, typically bear the brunt of recessions because of the stronger cyclicality of their employment and wages relative to women's. We study the extent to which fiscal policy may offset or worsen these asymmetric effects across gender. Using micro-level data for the U.S. from the Current Population Survey, we find that the effects of fiscal policy shocks on labor market outcomes depend on the type of public expenditure. Women benefit most from increases in the government wage bill, while men are the main beneficiaries of higher investment spending. Our analysis further reveals that the fiscal component most efficient at closing gender gaps is least suitable for offsetting inequitable business cycle effects across other socioeconomic dimensions.
Keywords: 330; Business cycles; Fiscal policy; Gender gaps; Heterogeneous labor market outcomes